Inflation expectations and the Phillips curve: An encompassing framework - Alexis Maka; Fernando de Holanda Barbosa (Institute for Applied Economic Research (ipea), 2017)
This paper contrasts empirically four leading models of inflation dynamics - the accelerationist Phillips curve (APC), new Keynesian Phillips curve (NKPC), hybrid Phillips curve (HPC) and sticky information Phillips curve (SIPC). We employ an encompassing Phillips curve specification that allows us to derive tests for these models within a single framework. Using the generalized method of moments (GMM) estimator, the evidence suggests that the restrictions implied by the NKPC, HPC, and SIPC are rejected for the U.S. during the Great Moderation. Only the restrictions implied by the APC are not rejected. When we use methods that are robust to the issue of weak instruments in GMM, the confidence regions are so wide that it is not possible to reject any models' restrictions, meaning that the evidence is consistent with all four models of inflation dynamics.
Keywords: E12; E31; E32; 330; Phillips curves; weak instruments; fully robust confidence regions